Thrombotic event prevention in patients with post-infarction chronic heart failure, as а part of complex therapy including various classes of beta -adrenoblockers - Yu. V. Larina; L. A. Nekrutenko; A. V. Tuev; A. V. Agafonov; I. P. Rubesh (Кардиоваскулярная терапия и профилактика)
Aim. To compare carvedilol and metoprolol tartrate effects on hemostasis in patients with post-infarction chronic heart failure (CHF), receiving complex therapy. To study deep venous thrombosis (DBT) incidence in CHF patients without additional risk factors (RFs) for venous thrombosis.Material and methods. The study included 60 patients, aged 60,58±8,16 years, with Functional Class (FC) II and III CHF (CHF duration 5,17±4,83 years). The main group (n=30) received carvedilol (44,17±7,86 mg/d at the end of follow-up), and the comparison group (n=30) - metoprolol (110,0±39,17 mg/d). Hemostasis parameters and DVT signs were assessed at baseline and after 4 months of the treatment.Results. In the hospital, laboratory thrombophilia was verified in all CHF patients. After 4 months of the therapy, positive hemostasis dynamics was observed in both main and comparison groups. One case of calf DVT, without pulmonary artery thromboembolia, was registered in a female with FC III CHF, who received metoprolol.Conclusion. Additional blockade of alpha-1-receptors and antioxidant activity of carvedilol could explain better hemostasis control in patients from carvedilol group.